A multiple case study of selected U.P. Diliman dormitory lobbies a study on third place theory - Gan, Jacqueline T. (College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The purpose of this study was to explore whether a dormitory lobby can be a potential third place. This was a multiple case study that focused on the lobbies of three (3) female dormitories in UP-Diliman. It utilized data collection methods such as observation, photo documentation and survey and corresponding instrumentation such as an observation guide, an Apple iPhone 4s, and a two-page survey questionnaire. Twenty (20) student residents from each of the three (3) dormitories were chosen to be the survey respondents of the study using convenience sampling. Results show that the most common activities performed in the three (3) lobbies were personal and academic-related activities and most respondents used the lobbies only because of convenience. Overall, the physical aspects of the lobbies were rated satisfactory by the respondents however, half of the respondents were not satisfied with their respective dormitory lobbies. ?Cleanliness? obtained the highest overall rating among the physical aspects of the lobbies while the most common problems were uncomfortable furniture and lack of furniture. In terms of the social aspects of the lobbies, most respondents were not able to associate their lobbies with all the eight (8) characteristics of a third place as established by Oldenburg (1999). In conclusion, the three (3) lobbies cannot be considered third places since the respondents did not view the lobbies as separate from their first place (home) and second place (work) where they are able to escape and unwind. Instead they viewed them only as convenient spaces where they can perform personal activities and academic-related activities. Most of the respondents were not able to develop an attachment to these spaces.